2013
DOI: 10.1016/j.theriogenology.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Cryoprotective effect of different glycerol concentrations on domestic cat spermatozoa

Abstract: Cryopreservation of spermatozoa is a pivotal tool in assisted reproduction, and studies aiming to establish optimal freezing/thawing protocols are essential to enhance sperm survival. The objectives of the present study were to (1) compare the cryoprotective efficiency of three different glycerol concentrations (3%, 5%, and 7%) on the basis of post-thaw sperm quality and (2) investigate whether the incidence of morphologically abnormal sperm in fresh samples is related to cryodamage sensitivity. Semen was coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 34 publications
4
24
1
3
Order By: Relevance
“…The subsequent fast cooling step from 10 or even 15 to 4°C, which was in our case already part of the freezing process over liquid nitrogen, was well tolerated by cat epididymal sperm. In the samples only cooled to 15°C, the velocity of progressive sperm after cryopreservation was the only parameter which was immedi- AE 12 (Villaverde et al 2013) ately after thawing significantly reduced in relation to samples which had been further cooled to 10°C (and in relation to initial values). On the contrary, the linearity of progressive sperm after thawing was higher after cooling to only 15 than to 10°C.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The subsequent fast cooling step from 10 or even 15 to 4°C, which was in our case already part of the freezing process over liquid nitrogen, was well tolerated by cat epididymal sperm. In the samples only cooled to 15°C, the velocity of progressive sperm after cryopreservation was the only parameter which was immedi- AE 12 (Villaverde et al 2013) ately after thawing significantly reduced in relation to samples which had been further cooled to 10°C (and in relation to initial values). On the contrary, the linearity of progressive sperm after thawing was higher after cooling to only 15 than to 10°C.…”
Section: Discussionmentioning
confidence: 88%
“…Cooling rates between À0.5 and À0.1 K/min were probably used in most studies even if exact rates and final temperatures achieved during cooling are not always reported in detail. However, (Villaverde et al 2013) used a faster cooling rate of À3.4 K/min and (Zambelli et al 2002) was successful with a cooling rate of À12 K/min in the presence of glycerol followed by a subsequent holding step at 4°C (Table 3). This holding step can be attributed to sperm equilibration with glycerol, to sperm adaptation to 4°C or both.…”
Section: Discussionmentioning
confidence: 99%
“…Iodixanol can be postulated to be a cryoprotectant similar to sugar, ethylene glycol and glycerol. Glycerol is widely accepted as having a lower freezing point in the intracellular process of spermatozoa in livestock (Villaverde et al 2013). In the present study, it was found that a low concentration of 2.50% iodixanol in the extender (together with glycerol in the TEY dilution) had a less toxic effect on the motility of frozen sperm; similar results have been previously reported (Saragusty et al 2009;Cirit et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Assim, recomenda-se para o gato, a adição do glicerol a 4ºC, a fim de minimizar os efeitos tóxicos do crioprotetor, em concentrações inferiores a 8%, sendo que o emprego deste a 5% confere melhor efeito crioprotetor à célula espermática (Deco- Souza et al, 2013;VillaVerde et al, 2013).…”
Section: Criopreservação Dos Espermatozoides Epididimáriosunclassified
“…Quanto à descongelação, várias são as temperaturas (37ºC, 38ºC, 42ºC, 65ºC, 70ºC) e tempos (6 a 30 segundos) propostos (Axner et al, 2004;Chatdarong et al, 2007;Cocchia et al, 2010;Vick et al, 2012;VillaVerde et al, 2013;Vizuete et al, 2014;Buranaamnuay, 2015;Thuwanut et al, 2015;Klaus et al, 2016;Kunkitti et al, 2016). A escolha do protocolo de descongelação dependerá da curva de congelação estabelecida, sendo assim, espermatozoides submetidos à refrigeração lenta são submetidos a tempo maior de descongelação (Buranaamnuay, 2017).…”
Section: Criopreservação Dos Espermatozoides Epididimáriosunclassified